"Invisible sportswomen": The sex data gap in sport and exercise science research - Cowley, E. S.; Olenick, A. A.; McNulty, K. L.; Ross, E. Z. (Women in Sport and Physical Activity Journal, 2021)
This study aimed to conduct an updated exploration of the ratio of male and female participants in sport and exercise science research. Publications involving humans were examined from The European Journal of Sports Science, Medicine & Science in Sport & Exercise, The Journal of Sport Science & Medicine, The Journal of Physiology, The American Journal of Sports Medicine, and The British Journal of Sports Medicine, 2014-2020. The total number of participants, the number of male and female participants, the title, and the topic, were recorded for each publication. Data were expressed in frequencies and percentages. Chi-square analyses were used to assess the differences in frequencies in each of the journals. About 5,261 publications and 12,511,386 participants were included in the analyses. Sixty-three percentage of publications included both males and females, 31% included males only, and 6% included females only (p < .0001). When analyzing participants included in all journals, a total of 8,253,236 (66%) were male and 4,254,445 (34%) were female (p < .0001). Females remain significantly underrepresented within sport and exercise science research. Therefore, at present most conclusions made from sport and exercise science research might only be applicable to one sex. As such, researchers and practitioners should be aware of the ongoing sex data gap within the current literature, and future research should address this.